Evaluasi Implementasi Kurikulum Merdeka Pada Pembelajaran Bahasa Arab Kelas X di MAN 1 Gresik - Ikhwanul Habib; Kabalmay, Taqiyuddin (Fakultas Keguruan dan Ilmu Pendidikan Universitas Samawa, 2025)
The curriculum is fundamental in the implementation of learning. The curriculum as a plan that leads to national education goals has developed over time. This writing aims to evaluate the implementation of the Arabic curriculum at MAN 1 Gresik whether the application of the independent curriculum is appropriate and describes the content of learning outcomes, the flow of learning objectives and the teaching modules used. The method used in this research is qualitative. Data collection techniques are observation, interview, and documentation. Data analysis techniques use data reduction stages, present data and draw conclusions. Data validity uses triangulation. The result of this study is that in the context of Arabic language learning at MAN 1 Gresik, the implementation of the Merdeka Curriculum has run in accordance with the principles of the curriculum. Learning outcomes, flow of learning objectives, and teaching modules have been systematically designed and adapted by subject teachers. In addition, the assessment is carried out thoroughly to evaluate all elements of learning mandated in the curriculum, both aspects of knowledge, skills, and attitudes. This success is also supported by teacher readiness, availability of facilities and infrastructure, and school management support.